A Numerical model of Rotorua Geothermal Field. (March 2016) - Ratouis, Thomas M.P.; O'Sullivan, Michael J.; O'Sullivan, John P.
Highlights: Paper describes current knowledge of the geology, geophysics and fluid chemistry. A numerical model of the RGF is developed to study its response to production history. The 3D grid allows for explicit representation of faults and geothermal surface features. Temperatures, pressures, surface heat flows, Cl and CO2 data are used for calibration. Reservoir modelling can match the system recovery after the bore closure programme. Abstract: The Rotorua geothermal field is a shallow geothermal reservoir lying directly beneath Rotorua Township in New Zealand. Temperatures of up to 200 °C have been recorded at depths of less than 100 m. It is renowned for its abundance of natural geothermal manifestations including the geysers and hot springs at Whakarewarewa. The combination of the close proximity of the resource to a population centre and ease of access for end-users led to intensive extraction of the geothermal fluid for domestic, commercial and industrial usage in the 1970s. This resulted in a general decline of the activity of the surface features and in 1982 an extensive Monitoring Programme was initiated. This was followed by a Bore Closure Programme in 1986, aimed at restoring surface activity. Geysers and hot springs have since rejuvenated progressively with some springs overflowing recently for the first time in over 30 years. It is an interesting feature of the history of the Rotorua Geothermal Field that over-exploitation was acknowledged and subsequently addressed by changes in the management and allocation of the resource. The data collected during the decline and the recovery of the system offer a unique opportunity to study the effect of both unregulated and regulated extraction schemes on the health of a system and to determine the extent of surface manifestation recovery after a step-change decrease in fluid abstraction. A three-dimensional numerical model of the Rotorua system, called here UOA Model 4a, has been developed to study the response of surface features to production and reinjection. It differs from previous models by featuring a higher level of refinement and complexity. The model includes the vadose zone and has a fine layer structure in the shallow zone, which enables a better representation of near-surface mass and heat flows. Natural state and production simulation runs were carried out using the EWASG equation of state (non-isothermal mixtures of water, sodium chloride and a non-condensible gas) in the numerical simulator AUTOUGH2, the University of Auckland's version of TOUGH2. UOA Model 4a was calibrated using the available chloride and CO2 data in addition to temperatures, pressure transients and surface heat and mass flows. The results show that the model provides a valuable tool for representing and understanding the behaviour of the Rotorua system and assisting with future management of the resource.